Sekolah Terpadu: Polarisasi Sistem Pendidikan Indonesia - faizin faizin (At-Tarbiyat, 2019)
In contrast to pesantren, madrasa is a follow-up of religious education in pesantren, where 30% of the subjects are religious, then general subjects are followed. In the last 20 years, pesantren have adopted many madrasa education systems by including general subjects in their teaching systems.The introduction of the madrasa system was carried out to bridge the gap between the pesantren education system and the school education system, which in turn led to a dualism of the system in national education. Emphasis on pesantren education in religious subjects, often reponsented unable to face the era of 5.0. Islamic-based integrated schools emerged and became a new offer in the discourse of the development of formal education institutions in Indonesia.As an indication of this phenomenon is a discussion of the educational model in Indonesia from the time Indonesia was established until the late 20th century, consisting only of public and religious schools (read: pesantren). Public schools in Indonesia are a legacy of Dutch colonizers whose teaching includes general sciences such as natural sciences, engineering sciences, social sciences, and English. Islamic boarding schools are traditional Islamic educational institutions with characteristics in which there are mosques, kyai, santri, and the teaching of the yellow book.Islamic boarding schools, at first, only taught 100% of religious subjects. The purpose of education in pesantren is to produce religious scholars. The existence of an Islamic-based integrated school has become an igniter of educational ideology in Indonesia